(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates the impact of Perceived Social Relationships (PSR) through Instagram influencer marketing on consumer decisions and the sales performance of beauty and cosmetic brands in Nepal. A mixed-method approach, combining quantitative surveys and qualitative interviews, was employed. The quantitative data, collected from Instagram users and beauty brand consumers, was analyzed using descriptive and inferential statistics, while the qualitative data provided insights from social media influencers and brand managers. The findings reveal that advertisements (Ads), personal engagement (PE), and interaction with influencers significantly affect consumer buying intentions, with interaction being the most influential. Information content (IC), however, showed a weak and statistically insignificant relationship with consumer buying intentions. These results emphasize the importance of engagement-driven strategies in influencer marketing. The study suggests that brands should prioritize authentic, interactive content to enhance consumer trust and purchase intent. The novelty of this research lies in its contextual focus on Nepal, offering new insights into the dynamics of influencer marketing in an emerging market.